2013
DOI: 10.3389/fnhum.2013.00268
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated left inferior parietal activity in schizophrenia and depression: functional connectivity and characterization

Abstract: The inferior parietal cortex (IPC) is a heterogeneous region that is known to be involved in a multitude of diverse different tasks and processes, though its contribution to these often-complex functions is yet poorly understood. In a previous study we demonstrated that patients with depression failed to deactivate the left IPC during processing of congruent audiovisual information. We now found the same dysregulation (same region and condition) in schizophrenia. By using task-independent (resting state) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 88 publications
2
55
0
Order By: Relevance
“…Abnormal FC in left IFG, MiFG, and IFG was found in SZ patients (Jeong et al, 2009; Müller et al, 2013). …”
Section: Discussionmentioning
confidence: 92%
“…Abnormal FC in left IFG, MiFG, and IFG was found in SZ patients (Jeong et al, 2009; Müller et al, 2013). …”
Section: Discussionmentioning
confidence: 92%
“…That is, we tested whether the conditional probability of activation given a particular label [P(Activation|Task)] was higher than the baseline probability of activating the region in question per se [P(Activation)]. Significance was established using a binomial test (p < .05, corrected for multiple comparisons using FDR; Müller et al, 2013; Rottschy et al, 2013). In the reverse inference approach, the functional profile was determined by identifying the most likely behavioral domains and paradigm classes given activation in a particular region.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, lPFC activation would reflect that processing of stimuli that are identified as familiar may engage a more exhaustive search for details, which suggests more detailed processing of familiar stimuli (Wheeler & Buckner, 2004). In contrast, it has been suggested that the mPFC may belong to a system (in association with amygdala and ACC) that exerts emotion-driven influences on action selection (Ernst & Paulus, 2005;Müller, Cieslik, Laird, Fox, & Eickhoff, 2013;Ridderinkhof, Van den Wildenberg, Segalowitz, & Carter, 2004). Thus, both in the paradigms with and without encoding, activations within the lPFC (i.e., the inferior frontal gyrus) may be associated with the cognitive assessment of familiarity, whereas those within the medial PFC (mPFC) may reflect affective appraisal (Ernst & Paulus, 2005;Martínez-Selva, Sánchez-Navarro, Bechara, & Román, 2006;Ridderinkhof et al, 2004).…”
Section: Common Activations For Paradigms With and Without Encoding Umentioning
confidence: 99%